PERSEPSI DAN MOTIVASI MASYARAKAT TERHADAP PRAKTIK MENABUNG DI LEMBAGA KEUANGAN SYARIAH - Agus Makinuddin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2026)
Abstrak This study aims to explore the public's perception and motivation in choosing to save in Islamic financial institutions, focusing on BMT UGT Nusantara Ngoro Branch. Using a qualitative case study approach, data were collected through in-depth interviews with BMT members from various social and economic backgrounds. The results of the study indicate that public perception of Islamic principles, trust in fund management, and conformity with religious values ​​are the main factors in shaping savings decisions. In addition, economic motivations such as fund security and ease of transactions are also important considerations. Social values ​​and the role of religious figures also strengthen public confidence in choosing Islamic financial institutions. These findings indicate that savings decisions are not solely based on financial aspects, but are also influenced by ideological, emotional, and social factors. This study provides insight for BMT managers to understand customer mindsets and design a more contextual and value-based service approach.